2014
DOI: 10.1055/s-0034-1384825
|View full text |Cite
|
Sign up to set email alerts
|

MR Arthrography of the Shoulder: Technical Update and Clinical Applications

Abstract: Direct MR arthrography of the shoulder is a safe, relatively easy procedure that can increase diagnostic confidence in the evaluation of rotator cuff and labroligamentous disorders compared with conventional MR imaging of the shoulder. Surgeons more often request MR arthrography in younger patients who may have internal impingement or subtle shoulder subluxation rather than obvious cuff rupture, repeated dislocation, or arthropathy. This article describes the advances in glenohumeral injection and MR protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…1 A previous study demonstrated 98% sensitivity and 96% specificity for MRI detection of full-thickness rotator cuff tears, as compared with arthroscopy.…”
Section: Introductionmentioning
confidence: 93%
“…1 A previous study demonstrated 98% sensitivity and 96% specificity for MRI detection of full-thickness rotator cuff tears, as compared with arthroscopy.…”
Section: Introductionmentioning
confidence: 93%
“…Findings suggestive of a SLAP tear include a high signal intensity that is globular, irregular or laterally curved into the substance of the labrum on coronal oblique images, an anterior to posterior linear hyperintense signal on axial T1-weighted MR arthrography (MRA), a signal of irregular width measuring > 2 mm. Because contrast material or joint fluid will extend under the free edge of a meniscoid-type superior labrum, it may be mistaken for a labral tear [ 1 3 4 11 14 21 25 26 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 ].…”
Section: The Labrummentioning
confidence: 99%
“…These anterosuperior variants may also predispose to superior labral lesions. Differentiating these normal variants from pathology is crucial because fixing the normal labrum and/or the middle glenohumeral ligament will result in loss of external rotation and surgical failure [ 1 3 9 14 25 30 32 33 34 35 36 37 38 39 40 44 46 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 ].…”
Section: The Labrummentioning
confidence: 99%
See 2 more Smart Citations